(3GdCfhGA hGdCRefI heYQaI CYjGf GdchGcHs - (3YHO Gddg Hf MSjf Hf YGUes ((3eMeO Hf CMeO Hf SdjeGf GdJLjHj s)
(3ChdgG (B:s
(3bGd YHO Gddg (B: (3gPG cJGH LeYJ ajg eG JYde Hg ePGgH GdYQH ai JSejI GdSeGA hadcgG hbWHgG hHQhLgG hefGRdgG hGdeTghQ ef SGFQ fLhegG , heYfi GdeQGbHI hGdeWGdYI ajgG s
(3BNQgG (B:s
(3hcGf GdSMhQ GdChd jWGdY GdGcdjd , hGdSMhQ GdKGfi jWGdY GdbdH , hGdaLQ jWGdY GdThdI Je GdcJGH hGdMeO ddg s
(3HChdgG eWGdYI SfI (B851(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs